Microtubule-associated nuclear envelope proteins in interphase and mitosis. (21st November 2011) - Figueroa, Ricardo A.; Gudise, Santhosh; Hallberg, Einar
Abstract : The LINC (linker of nucleoskeleton and cytoskeleton) complex forms a transcisternal bridge across the NE (nuclear envelope) that connects the cytoskeleton with the nuclear interior. This enables some proteins of the NE to communicate with the centrosome and the microtubule cytoskeleton. The position of the centrosome relative to the NE is of vital importance for many cell functions, such as cell migration and division, and centrosomal dislocation is a frequent phenotype in laminopathic disorders. Also in mitosis, a small group of transmembrane NE proteins associate with microtubules when they concentrate in a specific membrane domain associated with the mitotic spindle. The present review discusses structural and functional aspects of microtubule association with NE proteins and how this association may be maintained over the cell cycle.